Gender-Responsive Construction in Nikah-Kawin Traditions in West Java: A Qiwamah Perspective - Sofiana, Neng Eri; Huda, Miftahul; Ismah, Nor; Purnomo, Agus; Aminuddin, Luthfi Hadi (Sharia Faculty of State Islamic Institute (IAIN) Palangka Raya, 2024)
Nikah-Kawin, a deeply rooted traditional marriage in West Java, has been passed down through generations in indigenous communities. This marriage differs from conventional marriage practices in several ways. In particular, women are given greater rights of choice, with some even taking on the responsibility of reciting the marriage vows. The article aimed to explore the gender-responsive construction in the nikah-kawin tradition of West Java communities through the concept of qiwamah. Using empirical legal research methods, this study utilizes primary data obtained from interviews, observations, and documentation. The findings reveal a gender-responsive construction shaped by the principles of qiwamah embedded in the nikah-kawin tradition of West Java communities. Interestingly, this constructed gender dynamic contributes to the formation of an egalitarian household environment. The presence of traditional guidelines upheld by these communities underscores their commitment to respecting and valuing women within the societal framework. This exploration highlighted how the uniqueness of nikah-kawin not only endures but also fosters a balanced and egalitarian approach to household life.